2018
DOI: 10.2147/ccide.s134315
|View full text |Cite
|
Sign up to set email alerts
|

Mineral trioxide aggregate pulpotomy: patient selection and perspectives

Abstract: This narrative aims at reviewing the available literature for mineral trioxide aggregate (MTA) pulpotomy to understand the procedure better and eventually improve the clinical and radiographic outcomes. An electronic search was conducted in PubMed, Cochrane, ScienceDirect and ClinicalKey databases with the following keywords: MTA pulpotomy, clinical outcomes, radiographic outcomes, primary teeth. No specific inclusion or exclusion criteria were applied as to what articles would be included in this review. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Condenser size in the present study had a diameter of 1.0 mm on the smaller end and 2.0 mm on the larger end so that the mixed material is adapted properly to all cavity walls, margins, and line angles. In addition to mechanical condensing tools, the wet cotton pellet can be used separately or in combination with hand condenser to place the pulpal medicament ( Musale et al, 2018 ). Group II and the second step of group III in the current study, a smaller pellet size was applied to facilitate ZOE packing.…”
Section: Discussionmentioning
confidence: 99%
“…Condenser size in the present study had a diameter of 1.0 mm on the smaller end and 2.0 mm on the larger end so that the mixed material is adapted properly to all cavity walls, margins, and line angles. In addition to mechanical condensing tools, the wet cotton pellet can be used separately or in combination with hand condenser to place the pulpal medicament ( Musale et al, 2018 ). Group II and the second step of group III in the current study, a smaller pellet size was applied to facilitate ZOE packing.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate material thickness in the case of pulpotomy amounts up to 3–4 mm. The thickness and compaction of the MTA layer can be assessed with X-ray [ 49 ]. The coronal excess of material should be removed with use of cotton pellet or mechanically with burs.…”
Section: Presentation Of Casesmentioning
confidence: 99%
“…The success of the calcium silicate and calcium aluminate cements for vital pulp therapy, including pulpotomies in permanent teeth, may delay or avoid root canal therapy. 103,257,262,263 Several pulpotomy studies reported 127,[264][265][266][267][268][269][270][271][272][273][274] highly successful outcomes using the calcium silicate cement products. Other studies compared the calcium silicate cements to the former standard of care in primary tooth pulpotomies (formocresol) [275][276][277] showing the equality or superiority of the calcium silicate cements for various pediatric dental procedures.…”
Section: Pulp Tissue Treatmentsmentioning
confidence: 99%